PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Septiana, Lidya; Masniladevi, Masniladevi; Zen, Mulyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of the use of problem based learning models on mathematics learnig outcome of studens in grade v studens of public elementary schools 07 silaing bawah padang panjang city in the 2018/2019 scholl year. This type of research is an experimental design study with the form of pretest-posttest control group design. The study was conducted in class V SDN 07 Silaing Bawah City of Padang Panjang, class IVA as a Control class and class IVB as an Experiment class with 25 students each. The research instrument used was a written test with multiple choice types. Based on the results of the t-test calculation which shows that the price of t count is greater than the table (2.137> 1.677). keywords: Problem Based Learning Model (PBL), Learning Outcomes, FractionsThis study aims to determine the effect of the use of problem based learning models on mathematics learnig outcome of studens in grade v studens of public elementary schools 07 silaing bawah padang panjang city in the 2018/2019 scholl year. This type of research is an experimental design study with the form of pretest-posttest control group design. The study was conducted in class V SDN 07 Silaing Bawah City of Padang Panjang, class IVA as a Control class and class IVB as an Experiment class with 25 students each. The research instrument used was a written test with multiple choice types. Based on the results of the t-test calculation which shows that the price of t count is greater than the table (2.137> 1.677). keywords: Problem Based Learning Model (PBL), Learning Outcomes, Fractions